Analysis of Stakeholders Collaboration Model and Its Impact on Improving Human and Natural Resources in the Independent Village Peat Care–Korea-Indonesia Forest Cooperation Center Program - Owin Jamasy, Djamaludin; Gyun, Kim Hyoung; Kusumah, Uus Danu; Khairun Nisa, Mohd Arshad (2023)
The protection and management of peat ecosystems is a systematic, integrated and effective measure, with the aim of preserving peat ecosystem functions and preventing damage to peat ecosystems. Preventing drought and peatland fires that often occur in Muaro Jambi and Tanjung Jabung Timur Regencies in Jambi Province is an important task of protecting and managing peat ecosystems for the purpose of maintaining hydrological functions, biogeochemical protection, biodiversity protection and productivity of peatlands which have the potential to become a source of life for all. living things. Such is the importance of this activity, that the Government of Indonesia through the Ministry of Environment and Forestry has launched the Independent Village Peat Care (IVPC/DMPG[1]) program. KIFC's contribution to support the IVPC program is through an empowerment, gender-sensitive and stakeholder collaboration approach. At the village level, a Working Team for Protection and Management of Peat Ecosystems (WT-PMPE/TK-PPEG[2]) was formed in 10 villages in Muaro Jambi and Tanjung Jabung Timur Regencies. The concrete program for WT-PMPE assisted by the Village Facilitator from KIFC is to provide assistance, training and funding to the WT-PMPE Work Plan for productive business activities such as farming on peatlands, cultivating fish and livestock. Overall, the stakeholder empowerment and collaboration approach model implemented by KIFC has had a significant impact on improving human and natural resources.